Clima Organizacional: pesquisa em hospital localizado no norte do Rio Grande do Sul - Mazzucato, Cíntia Savana (2022)
This article aims to evaluate the organizational climate of a hospital located in the north of the state of Rio Grande do Sul. The research that underpins this work has a quantitative and descriptive approach, being based on experiences lived during the internship at a health institution and also on data collection carried out through a questionnaire intended for employees. As a result of the research, it is evident that the organizational climate in the hospital is good and becomes an important factor for the proper functioning of a company, providing an environment that values and respects its employees, thus enabling the provision of a quality service for all.